2009
DOI: 10.1523/jneurosci.6144-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Hindbrain Cocaine- and Amphetamine-Regulated Transcript Induces Hypothermia Mediated by GLP-1 Receptors

Abstract: Cocaine-and amphetamine-regulated transcript (CART) peptides are widely distributed throughout the neuraxis, including regions associated with energy balance. CART's classification as a catabolic neuropeptide is based on its inhibitory effects on feeding, coexpression with arcuate nucleus proopiomelanocortin neurons, and on limited analysis of its energy expenditure effects. Here, we investigate whether (1) caudal brainstem delivery of CART produces energetic, cardiovascular, and glycemic effects, (2) forebrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 59 publications
(93 reference statements)
1
29
0
Order By: Relevance
“…In the present study, in line with earlier studies (42,45,46), we found that EX4 reduced body temperature in the rat. Surprisingly, combined (but not single) blockade of IL-6 and IL-1 partly reversed the hypothermic effect of GLP-1R activation.…”
Section: Il-1r1supporting
confidence: 94%
“…In the present study, in line with earlier studies (42,45,46), we found that EX4 reduced body temperature in the rat. Surprisingly, combined (but not single) blockade of IL-6 and IL-1 partly reversed the hypothermic effect of GLP-1R activation.…”
Section: Il-1r1supporting
confidence: 94%
“…Therefore, energy expenditure was quantified as the average core temperature and activity beginning 1.5 h after the injection (when activity levels stabilized) until the end of the 6.5-h recording period. As described previously, food was not available during the period of energetic response measurement to avoid diet-induced thermogenesis, which could have confounded the interpretation of the effects of BDNF on energy expenditure (47,49). Food intake and body weight measurements were made immediately before and 24 h after the injection of the drug.…”
Section: Methodsmentioning
confidence: 99%
“…Rats received a guide cannula (22-gauge; Plastics One, Roanoke, VA) with its tip positioned stereotaxically 2.0 mm above either the 4th ventricle (coordinates: on the midline, 2.5 mm anterior to the occipital suture and 5.2 mm ventral to the skull, with injector aimed 7.2 mm from skull) or the medial NTS at the level of the AP (coordinates: midline Ϯ 0.75, 1.0 mm posterior to the occipital suture and 6.9 mm ventral to the skull, with injector aimed 8.9 mm from skull) (20,21,47,48,51). Cannula were attached to the skull with dental acrylic and jeweler's screws and closed with obturators.…”
Section: Surgerymentioning
confidence: 99%
“…For the NAcc shell, the following coordinates were used (modified from (Quarta et al, 2009): ±0.75 from the midline, 1.7 mm anterior to bregma, and 6.0 mm ventral to skull, with injector aimed 7.5 mm ventral). Cannulae were attached to the skull with dental acrylic cement and jeweler's screws and closed with an obturator, as described previously (Skibicka et al, 2009). In all rats, the microinjection site for both VTA and NAcc was verified post mortem, by microinjection of India ink at the same microinjection volume (0.5 μl) used throughout the study.…”
Section: Surgerymentioning
confidence: 99%